2020
DOI: 10.2807/1560-7917.es.2020.25.19.2000620
|View full text |Cite
|
Sign up to set email alerts
|

Mortality impacts of the coronavirus disease (COVID-19) outbreak by sex and age: rapid mortality surveillance system, Italy, 1 February to 18 April 2020

Abstract: Data from the rapid mortality surveillance system in 19 major Italian cities were used to carry out a timely assessment of the health impact of the COVID-19 epidemic. By 18 April, a + 45% excess in mortality was observed, with a higher impact in the north of the country (+ 76%). The excess was greatest among men, with an increasing trend by age. Surveillance data can be used to evaluate the lockdown and re-opening phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
86
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 13 publications
(18 reference statements)
9
86
2
4
Order By: Relevance
“…In the subgroup of the population of males 65–79 and ≥ 80 slight increases in death rates were observed from week 9 to 15, but still similar to rates in previous years. Despite this small change, it did not have an effect of overall causing excess mortality in the population, even though other studies have found that elderly men are at increased risk of death [ 7 ]. There was no marked change in death rates among those with comorbidities, which following a peak declined gradually, suggesting that no collateral damage has occurred due to lockdown, or restrictions in hospital services.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the subgroup of the population of males 65–79 and ≥ 80 slight increases in death rates were observed from week 9 to 15, but still similar to rates in previous years. Despite this small change, it did not have an effect of overall causing excess mortality in the population, even though other studies have found that elderly men are at increased risk of death [ 7 ]. There was no marked change in death rates among those with comorbidities, which following a peak declined gradually, suggesting that no collateral damage has occurred due to lockdown, or restrictions in hospital services.…”
Section: Discussionmentioning
confidence: 96%
“…Monitoring of total mortality is recommended, as not all deaths occur in hospitals [ 6 ]. Italy reports a 45% excess total mortality, highest in the North [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the initial phase of the pandemic, the outbreak in Italy seemed to have a greater severity of the disease, with a higher case fatality rate (CFR) than previously observed in China (7.2 vs. 2.3%) [35]. The excess in COVID-19 mortality was higher in men than in women living in northern cities versus in central and southern Italy (men: +87% and +70% and women: + 17% and + 9%, respectively), with an increasing trend by age [36].…”
Section: Introductionmentioning
confidence: 85%
“…The total score is calculated by adding together the response values of each item, with higher scores indicating more severe levels of depressive, anxiety, and stress symptoms. The score at the DASS-depression subscale (e.g., "I felt that I had nothing to look forward to") is divided into normal (0-9), mild (10)(11)(12), moderate (13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The score at the DASS-anxiety subscale (e.g., "I was worried about situations in which I might panic and make a fool of myself") is divided into normal (0-6), mild (7-9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe anxiety .…”
Section: Assessment Toolsmentioning
confidence: 99%
See 1 more Smart Citation